Survey Tingkat Keterampilan Teknik Dasar Passing Bola Basket pada Ekstrakulikuler di Sekolah Menengah Atas Kabupaten Bungo - Ahmad Nurkholis; Ikhsan Maulana Putra; Titis Wulandari (CV. Master Literasi Indonesia, 2025)
Abstrak: This research was motivated by the low performance of high school basketball teams in Bungo Regency, despite regular training. Observations revealed errors in basic passing techniques, suspected to be influenced by the quality of training, attitude, and physical condition. This study aimed to determine the passing skill levels (chest pass, bounce pass, and overhead pass) among students at SMAN 2 Bungo, SMAN 12 Bungo, and SMK Setih Setio 2 Bungo. The research method used a quantitative survey approach. The sample consisted of 49 athletes using a total sampling technique. Data were obtained through passing skills tests and analyzed descriptively. The results showed that the passing skill levels were generally in the